Antiquities. A Description of the Classics Department Museum in The Australian National University, Canberra - Green, J. R. (1981)
KeiBi-relevant: p. 11-14: Material from the Late Bronze Age Temple at Amman (cf. PEQ 98, 155-162; ZATW 78, 351-359; Levant 6, 131-178; PEQ 104, 17-32), esp. in v. 75.16, cylinder seal of lapis lazuli.